Shatter me - Mafi, Tahereh (Mafi, Tahereh. Shatter me series, 2011)
Ostracized or incarcerated her whole life, seventeen-year-old Juliette is freed on the condition that she use her horrific abilities in support of The Reestablishment, a postapocalyptic dictatorship, but Adam, the only person ever to show her affection, offers hope of a better future.